Long-term outcomes and cost-effectiveness evaluation of robot-assisted stereotactic hematoma drainage for spontaneous intracerebral hemorrhage - Tan, Ke; Peng, Yutao; Li, Jinping; Liu, Chang; Tao, Libo (Frontiers in Neurology, 2023)
Background To investigate the long-term follow-up and economic estimation outcomes of hematoma drainage for spontaneous intracerebral hemorrhage (SICH) with the assistance of neurosurgical navigation and positioning planning system (referred to as robot). Methods Data were retrospectively obtained from consecutive patients with SICH who were admitted to our single-center between March 2019 and March 2022. Different minimally invasive surgery (MIS) procedures were performed according to the inclusion/exclusion criteria. The different groups were sampled and matched using the propensity score method, with age, sex, history of stroke, hypertension, bleeding volume and site of bleeding as matching variables, and matched with inverse probability weighting using R statistical analysis software. From the time of discharge up until 1 year after the surgery, records were gathered on clinical results and medical expenditures. An analysis was conducted to compare the costs and health outcomes of both robot-assisted stereotactic hematoma drainage and neuro-endoscopic surgery, considering both short-term and long-term effects. Health outputs were measured using modified Rankin scale (mRS) and quality adjusted life years (QALYs). Results Of the 142 patients, there were 77 patients in the robotic surgery group and 65 patients in the neuro-endoscopic surgery group. Propensity score sampling was matched, resulting in a balanced and comparable group of 37 patients in each, with the robotic surgery group [mean age (57.29 ± 12.74) years, 27 males (72.97%), hematoma volume (44.54 ± 10.49 ml), 22 deep location (59.46%)] and the neuro-endoscopic surgery group [mean age (57.27 ± 11.12) years, 27 males (72.97%), hematoma volume (44.70 ± 10.86 ml), 23 deep location (62.16%)]. At both three-month and one-year postoperative follow-up, the proportion of mRS scores ≤3 was higher in the robotic surgery group (45.95%,70.27%) than in the neuro-endoscopic surgery group (35.14%, 62.16%), but there was no statistically significant difference (P = 0.344, 0.461). One year after surgery, the robotic group demonstrated cost savings of ¥36,862.14 per individual and a gain of 0.062 QALYs compared to the neuro-endoscopic group. Conclusion Our calculations based on a model for SICH suggest that robotic-assisted stereotactic drainage offers health economic benefits due to its lower cost and higher effectiveness. However, to confirm these findings, more data from multicenter, prospective randomized controlled trials with larger sample sizes are needed.